2018
DOI: 10.1111/pbr.12658
|View full text |Cite
|
Sign up to set email alerts
|

Zinc biofortification of maize (Zea mays L.): Status and challenges

Abstract: Zn deficiency is one of the leading health problems in children and women of developing countries. Different interventions could be used to overcome malnutrition, but biofortification is most impactful, convenient, sustainable and acceptable intervention. Maize is one of the major crops grown and consumed in the regions with prevalent Zn malnutrition; therefore, this is suitable target for Zn biofortification. Zn biofortification of maize could be achieved through agronomic and genetic approaches. Discussion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 177 publications
(299 reference statements)
2
81
0
Order By: Relevance
“…However, these studies did not clearly distinguish between the effects of soil Zn application and foliar Zn spraying. Soil and foliar applications have been reported to have differential effects on Zn concentrations of maize kernels [60]. Our study revealed that effects of various foliar treatments on maize grain Fe accumulation and bioavailability were similar to those on Zn.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…However, these studies did not clearly distinguish between the effects of soil Zn application and foliar Zn spraying. Soil and foliar applications have been reported to have differential effects on Zn concentrations of maize kernels [60]. Our study revealed that effects of various foliar treatments on maize grain Fe accumulation and bioavailability were similar to those on Zn.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, foliar Zn spraying should be adopted as an effective way to biofortify maize with Zn. However, to overcome Zn malnutrition, a Zn concentration of more than 37 mg/kg in the whole grain [60] and an increase of 30 mg/kg in the endosperm (www.harvestplus.org) of maize (because the major proportion of the maize grain is comprised of endosperm) are recommended. In terms of Zn bioavailability, the critical molar ratio of PA/Zn is 15-20; a value of 5-15 represents about 30-35% Zn availability, and ≥15 represents about 15% Zn availability [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of multiple grain samples from maize and wheat that have been collected by CIMMYT across environments and genotypes suggest that the levels of Fe and Zn are higher in wheat than in maize. However, we are not aware of any specific studies comparing wheat and maize mineral concentrations in the same experiment and in different grain tissues [43,44,45,20].…”
Section: Iron and Zinc Deficiencymentioning
confidence: 99%